Consumer Buying Behaviour in Indian Real Estate – Key Challenges and Opportunities: Understanding Consumer Buying Behavior in the Mumbai Real Estate Market (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The real estate sector is one of the most globally recognized sectors. In India, real estate is the second largest employer after agriculture and is expected to grow at 30 per cent over the next decade. Decisions for investment, buying and selling of properties depend on many factors such as pricing, product, location, amenities etc. Consumers buying behaviour is completely dependent on all above parameters and many real estate developers are facing key challenges in accommodating all of the above parameters. This sector is benefitted by the various initiatives of the Government like Pradhan Mantri Awas Yojana, Pradhan Mantri Gramin Awaas Yojana, Rajiv Awas Yojna, etc. aiming at providing a house to all citizens. It is thus, important for the companies in this sector to identify the buying behaviour of customers looking to buy flats with its associated challenges and opportunities. The present study has been carried out to understand different key challenges and opportunities of consumer buying behaviour with special reference to properties located in Mumbai region.